Simulation and Experimental Analysis of Stiffness and Damping of the Waist Type Diaphragm Coupling - Hong Yun; Wang Dan; Nong Su; Zhu Rupeng; Chen Weifang (Jixie chuandong)
The stiffness and damping characteristics of the diaphragm coupling are the basis for analyzing the vibration characteristics of the shafting system with the diaphragm coupling. Based on Ansys finite element simulation software, considering contact nonlinearity and large deformation effects, this study simulates and analyzes the torsional, axial, angular and radial static stiffness characteristics and torsional and axial dynamic characteristics of the diaphragm coupling, and analyzes the influence of the diaphragm structure parameters such as the diameter of the bolt hole distribution circle, the diameter of the bolt hole, the minimum width of the diaphragm and the thickness of the diaphragm on the static stiffness. Finally, static, dynamic torsion and axial tension tests are carried out to verify the correctness of the simulation results. The results show that the diameter of the bolt hole distribution circle and the thickness of the diaphragm have a greater influence on the anisotropic stiffness of the diaphragm. The dynamic model of the diaphragm coupling can be better established through the quasi elliptic function. The nonlinear stiffness and the equivalent damping coefficient changes in a period of the diaphragm vibration can be obtained.